2020
DOI: 10.1177/1358863x20964577
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in presentation, management, and outcomes among patients hospitalized with acute pulmonary embolism

Abstract: While the presence of gender disparities in cardiovascular disease have been described, there is a paucity of data regarding the impact of sex in acute pulmonary embolism (PE). We identified all patients admitted to a tertiary care hospital with acute PE between August 1, 2012 through July 1, 2018. We stratified the presenting characteristics, management, and outcomes between women and men. Of the 2031 patients admitted with acute PE, 1081 (53.2%) were women. Women were more likely to present with dyspnea (59.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0
13

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(43 citation statements)
references
References 23 publications
0
30
0
13
Order By: Relevance
“…Despite a higher age-adjusted incidence of PE in men, the patterns of developing PE vary with age among women and men [ 14 , 18 , 19 ]. Studies have suggested that women diagnosed with PE are more likely to be older than men [ 15 , 20 , 21 , 22 ]. In the 4-year study conducted by Choi et al evaluating sex differences in the incidence of PE in hospitalized patients, in patients > 50 years of age, PE was more frequent in women (incidence: 0.15%; 95%CI: 0.11–0.19%) compared to men (incidence: 0.08%; 05%CI: 0.05–0.11%; p < 0.01) [ 23 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite a higher age-adjusted incidence of PE in men, the patterns of developing PE vary with age among women and men [ 14 , 18 , 19 ]. Studies have suggested that women diagnosed with PE are more likely to be older than men [ 15 , 20 , 21 , 22 ]. In the 4-year study conducted by Choi et al evaluating sex differences in the incidence of PE in hospitalized patients, in patients > 50 years of age, PE was more frequent in women (incidence: 0.15%; 95%CI: 0.11–0.19%) compared to men (incidence: 0.08%; 05%CI: 0.05–0.11%; p < 0.01) [ 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…The investigators found a small but significant difference in the cumulative 5-year probability of recurrent VTE between the sexes (12.4% in men vs. 10.9% in women; p = 0.0001) [ 26 ]. Of note, despite a higher incidence of recurrent PE and overall age-adjusted incidence of PE, men with acute PE were, irrespective of whether first time or recurrent, were more likely to be taking an antiplatelet medication at the time of presentation [ 20 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…28 Pribish et al. 25 evaluated an American cohort and found that women with acute PE were more likely to have normal right ventricular (RV) size than men on echocardiography.…”
Section: Discussionmentioning
confidence: 99%
“…Acute pulmonary embolism (PE) is considered one of the major risk factors for development of CTEPH; approximately 70% of patients with CTEPH had prior venous thromboembolism in a previous study 22 . Sex differences have been investigated in Denmark, Sweden, and the United States, with findings that female sex was slightly more common (52%–53%) in cohorts of studies on the incidence of acute PE 23–25 . Outcomes after acute PE seemed to be similar between the sexes after adjustment for age and comorbidities, but the clinical presentations differed between men and women 25–27 .…”
Section: Discussionmentioning
confidence: 99%